Research Progress on the Toxicity and Detoxification of T-2 Toxin - SONG Jia; FAN Huan; YAN Xue; WANG Wen-jie; ZHAO Chen (Liang you shipin ke-ji, 2020)
T-2 toxin is a secondary metabolite produced by Fusarium spp., and belongs to the type A mycotoxins in the cephalosporins family. T-2 toxin is highly toxic, and it pollutes not only crops in the field,but also granary which leads the post-harvest lost of grain, furthermore, it causes huge damage to human and animal health. Therefore, it becomes world widely the target to be prevented and controlled in the food industry and livestock industry in recent years. At present, the research on the biological toxicity of T-2 toxin is more indepth, but it still lacks adequate study on detoxification of T-2 toxin, especially the biological detoxification. The harm, mechanism and physical, chemical and biological methods of detoxification of T-2 toxins were reviewed. Focusing on the acquisition of efficient detoxification enzymes and the development of detoxification processes are conducive to the healthy development of multiple industries in China, such as grain industry, livestock industry, and by-product deep processing.